Urban Poverty Alleviation Strategies to Achieve the Sustainable Development Goals - Asmi Rezkiah Tanjung; Firman Firman (Universitas Muhammadiyah Ponorogo, 2026)
This study explores the strategies implemented by the North Jakarta City Government to address extreme poverty in alignment with the Sustainable Development Goals (SDGs), using Kampung Apung in Muara Baru as a case study. Kampung Apung represents a severe case of structural poverty in urban coastal areas, characterized by limited access to clean water, sanitation, education, and healthcare services. Employing a qualitative method with a descriptive approach, data were collected through in-depth interviews with government officials, related agencies, and local residents. The findings reveal that the poverty alleviation strategies consist of four key aspects: organizational strategy, program strategy, resource support strategy, and institutional strategy. Despite some improvements in poverty rates, structural barriers persist, such as unequal access to assistance and misaligned program targeting. The study concludes that a more comprehensive and sustainable approach, along with enhanced inter-agency coordination, is essential for effectively addressing poverty in Kampung Apung and contributing to the achievement of the SDGs. Keywords: Extreme Poverty; Local Government Strategies; SDGs;